2008
DOI: 10.2174/157340508786404044
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Denoising for Optical Coherence Tomography: A Review and Evaluation

Abstract: Abstract:Recently emerging non-invasive imaging modality -optical coherence tomography (OCT) -is becoming an increasingly important diagnostic tool in various medical applications. One of its main limitations is the presence of speckle noise which obscures small and low-intensity features. The use of multiresolution techniques has been recently reported by several authors with promising results. These approaches take into account the signal and noise properties in different ways. Approaches that take into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 80 publications
(110 reference statements)
0
43
0
Order By: Relevance
“…This includes spatial [4], angular [5], polarization [6] and frequency [7] compounding techniques. As for post-processing, anisotropic diffusion-based techniques [3] and multi-scale/multi-resolution geometric representation techniques [8] are of high interest between scholars. Use of compressive sensing and sparse representation have also been explored in the past few years [9].…”
Section: Introductionmentioning
confidence: 99%
“…This includes spatial [4], angular [5], polarization [6] and frequency [7] compounding techniques. As for post-processing, anisotropic diffusion-based techniques [3] and multi-scale/multi-resolution geometric representation techniques [8] are of high interest between scholars. Use of compressive sensing and sparse representation have also been explored in the past few years [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms have been proposed in some literatures to handle the speckle noise. The denoising effect of the spatial domain methods, such as Lee filter and RKT filter which blurs the edge easily while dealing with an image of OCT, is not satisfied [1,2]. In the frequency domain methods, Adler et al first used the adaptive wavelet threshold denoising algorithm to realize the OCT retinal image denoising [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the algorithm will be invalid while handling the images of multi-direction. The review of the OCT image denoising methods indicated that the wavelet-based threshold denoising algorithm does better in OCT image denoising while preserving edges [1] [4].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Adler et al, Wagner et al, and Mayer et al, applied the discrete wavelet transform which provides the most compact representation, however, it has two main limitations which include the fact that it is not shift-invariant and not oriented in two dimensions. 4,[6][7][8] The dual-tree complex wavelet transform overcomes these limitations.…”
Section: Introductionmentioning
confidence: 99%